Some results on Bayes estimation under Linex loss function - Masoud Ganji; Fatemeh Gharari (Journal of Hyperstructures)
In this paper, we introduced straightforward formulas for the Bayes risk linked to the Linex loss function, which we then applied to estimate parameters of the normal, Poisson, and fractional Weibull distributions.We aimed to investigate the development of a linear Bayes estimator using the Linex loss function and successfully derived it for the normal and Poisson scenarios.We also demonstrated the process of creating empirical Bayes estimates using Linex loss and applied it to observed frequencies fn(x)$ produced by the Poisson-gamma model.